RIFM fragrance ingredient safety assessment, 4-(2-butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one, CAS registry number 13215-88-8. (15th July 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment. 4-(2-Butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that 4-(2-butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one is not genotoxic. Data on 4-(2-butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one provide a calculated margin of exposure (MOE) > 100 for the repeated dose toxicity endpoint. The reproductive and local respiratory toxicity endpoints were evaluated using the threshold of toxicological concern (TTC) for a Cramer Class I material, and the exposure to 4-(2-butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one is below the TTC (0.03 mg/kg/day and 1.4 mg/day, respectively). The skin sensitization endpoint was completed using the dermal sensitization threshold (DST) for reactive materials (64 μg/cm 2 ); exposure is below the DST. The phototoxicity/photoallergenicity endpoints were evaluated based on data; 4-(2-butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; 4-(2-butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one was found not to be persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., Predicted Environmental Concentration/Predicted No Effect Concentration [PEC/PNEC]), are <1. Highlights: 4-(2-Butenylidene)-3, 5, 5-trimethylcyclohex-2-en-1-one; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.